Ultrastructure of Extracellular Matrix of Pectoralis Major Muscle in Chicken (Gallus gallus domesticus) - Chavan, Yuvaraj; Dhoolappa M.; Lakshmishree K. T.; Ganga Naik. S. (Indian Journal of Veterinary Anatomy, 2024)
The skeletal muscle extracellular matrix (ECM) plays an important role in muscle fiber force transmission, maintenance, and repair. The ultrastructure of fresh and extra cellular matrix (ECM) of skeletal muscle in commercial and native chicken and their potential biomedical applications were undertaken in the present work. In the present study ECM of commercial and native chicken decellularized by using physical (freeze-thawing) and chemical (Triton X-100) approaches and successful in removing most cell nuclei while maintaining tissue structure and most fibrillar (collagen) and non-fibrillar (GAG's) extracellular matrix components. The collagen fibers were maintained after decellularization with Triton X-100, according to ultrastructure analysis. Physical appearance of the ECM was milky white after decellularization when compared to pink fresh skeletal muscle tissues. After effective decellularization, scanning electron microscopy demonstrated micropore formation while retaining the collagen fibrils intact.